Analisis Kinerja Keuangan sebagai Prediktor Harga Saham Sektor Properi yang Terdaftar di BEI 2020-2024 - Rendi Arlia Syifa ubadilah; Nur Ainiyah; Hari Setino (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study the analyze the influence of financial performance as a predictor of stock price in the property and real estate sector listed on the IDX for the 2020-2024 period, using a sample consists of 12 property companies. The financial performance variables used in this study include ROE, EPS, CR, and TATO. The result of show that simultaneously,all four variables have a significant effect on stock prices. Partially, only ROE, EPS, and TATO have a significant impact, while CR has no significant effect. The analysis methods include descriptive statistics, classical assumption tests, multiple linear regression, and F Satatistical tests. The findings confirm that profitability, particularly (ROE and EPS) and asset efficiency (TATO), are the factors consideres by investors when evaluating stocks in the property sector. The analysis methods used in this study include descriptive statistics to summarize the data, classical assumption tests to ensure the validity of the regression model, multiple linear regression to examine the relationship between the financial performance variables and stock prices, and F-statistical tests to evaluate the overall significance of the model. The findings suggest that profitability, particularly ROE and EPS, and asset efficiency, represented by TATO, are the key factors considered by investors when evaluating stocks in the property sector.These results imply that investors in the property and real estate sector prioritize financial performance metrics that reflect the company's ability to generate returns and utilize its assets effectively. Specifically, ROE and EPS serve as crucial indicators of profitability and are closely monitored by market participants. On the other hand, CR, which measures the company's short-term liquidity, does not appear to have the same level of influence on stock prices.